2015
DOI: 10.1007/s13280-015-0677-1
|View full text |Cite
|
Sign up to set email alerts
|

Radioecological impacts of tin mining

Abstract: The tin mining activities in the suburbs of Jos, Plateau State, Nigeria, have resulted in technical enhancement of the natural background radiation as well as higher activity concentrations of primordial radionuclides in the topsoil of mining sites and their environs. Several studies have considered the radiological human health risks of the mining activity; however, to our knowledge no documented study has investigated the radiological impacts on biota. Hence, an attempt is made to assess potential hazards us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…As mentioned above (Section 3.2), exposure to organic solvents through different routes has been revealed to cause human health threats, such as cancer and fatality. The excavation activity of tin mining and the disposal of tailings change the radionuclide compositions in soil, thus increasing the chance of radiological exposure of mine workers and nearby residents (Arogunjo et al 2009;Aliyu et al 2015). During bauxite mining for AlCl 3 catalyst production, the excavation activities release air pollutants, such as dust and fine particulate matters, that harm the respiratory and cardiovascular systems after inhalation (Abdullah et al 2016).…”
Section: Single Score Lca Resultsmentioning
confidence: 99%
“…As mentioned above (Section 3.2), exposure to organic solvents through different routes has been revealed to cause human health threats, such as cancer and fatality. The excavation activity of tin mining and the disposal of tailings change the radionuclide compositions in soil, thus increasing the chance of radiological exposure of mine workers and nearby residents (Arogunjo et al 2009;Aliyu et al 2015). During bauxite mining for AlCl 3 catalyst production, the excavation activities release air pollutants, such as dust and fine particulate matters, that harm the respiratory and cardiovascular systems after inhalation (Abdullah et al 2016).…”
Section: Single Score Lca Resultsmentioning
confidence: 99%
“…Scientific studies have shown that abandoned mining sites on the Jos Plateau act as potential sources of PTEs and could be present in the human food chain causing subsequent exposure (Aliyu et al 2015;. Recent studies focused mainly on environmental contamination of the Jos Plateau in the Northern, Southern, and Barkin-Ladi LGA regions (Gyang and Ashano 2010;Daniel et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The waste contaminated the surrounding environment and caused exposure to the biosphere through the leaching process. Regulation regarding tailings waste management is needed to protect humans and the environment (Aliyu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%